Pathogenetic complexes in treatment of patients with viral respiratory infections - Elena N. Popova; Liubov A. Ponomareva; Alina A. Chinova (LLC "MEDIAFORMAT", 2022)
According to WHO, the share of acute respiratory infections (ARVI) is about 70-90% of all infectious diseases. Despite their relatively short-term course, they suffer significant economic damage due to high turnover among the population and temporary disability. Especially since the end of 2019, when SARS-Cov-2 infection has taken priority and the attention of the entire global medical community. ARVI is a heterogeneous group of infectious diseases of the respiratory system caused by a huge number of viruses (there are more than 200 of them, among them: influenza virus, parainfluenza, respiratory syncytial virus, adenovirus, coronavirus and others). The symptoms and pathogenesis of the disease are similar in many ways (fever, cough, chest pain, myalgia, asthenia, headaches, anosmia and others), but there are also differences. The article discusses in detail the symptoms of acute respiratory viral infections (including COVID-19) and medicines, their components, which are most widely used in the epidemic period, and also provides a pathogenetic justification for the use. During the epidemic period (in Russia it lasts from October to March-April), the demand for various medicines (drugs) among the population traditionally increases. Since ARVI belong to a group of diseases, in relation to which a large proportion of self-prescribing drugs and cases of self-medication, it is of interest to consider in more detail the various drugs and components of drugs from the point of view of the pathogenesis of the disease.